Analysis of the level of disclosure of the mission statements of large Brazilian companies, - Junqueira,Emanuel (2021)
ABSTRACT The aim of this study was to verify the level of disclosure of the survival, growth, and profitability (SGP) construct in the mission statements of Brazilian companies and in the collective discourse of different economic sectors, classified according to the “Biggest & Best” Annual published by Exame Magazine. The research seeks to fill the gap in the field by studying the disclosure of the SGP construct in the mission statements of large Brazilian companies. Considering the mission statement as the genesis of strategic planning, an analysis of the disclosure of the SGP construct allows for a discussion of the relevance of the contribution of the mission statement to the elaboration, implementation, and monitoring of that planning. The benefit of a mission statement aligned with the strategic planning lies in adequate communication to the stakeholders regarding the long-term SGP goals, based on the assumption that comprehensive and objective communication minimizes the risks of failures during the management process. Collective subject discourse (CSD) was used to develop a qualification metric of the constitutive elements of the organizational mission statements, enabling it to be identified whether the Brazilian companies, grouped into different economic sectors, are smoothing, concealing, or omitting the construct formed by the SGP components in their mission statements. This study investigates the presence or not of the SGP components in the collective discourse of mission statements of 220 large Brazilian companies. Most of the companies analyzed in the sample do not include SGP in their mission statements and those that do discuss it with discursive vagueness, lacking clarity in their disclosure of the components. For the academia, this finding contributes to understanding the constituent components of the mission statements of large Brazilian companies. For organizations, the findings indicate the need to reflect on the content to be used in the formulation of their mission statements.